Fear Reflected In John Green's The Fault In Our Stars (2012): A Psychoanalytic Approach - Husna, Shabrina Nur, Dr. Phil. Dewi Candraningrum, M.Ed (2016)
This research intends to describe about Hazel Grace Lancaster's and Augustus Waters's fear. The objective of this study is to analyze this novel based on the Individual Psychoanalytic Approach. The researcher used two data sources: primary data and secondary data. The primary data source of the study is The Fault in Our Stars novel by John Green. Secondary data are the supporting data taken from literary books, and some articles related to the novel. The secondary data of the study are also taken from any information related to the novel. The method of data collection is the researcher employs the descriptive qualitative research based on Psychoanalythic Theory. Based on the analysis, the researcher gets some conclusions. This research shows that the problem by the major characters is their fear. This novel tells about Hazel Grace Lancaster's and Augustus Waters's fear after they were diagnosed with cancer at the very young ages. They live out their days with the fear of death, pain, and oblivion. They were trying to figure out how to overcome their fear. Keywords: The Fault in Our Stars, fear, oblivion, John Green, psychoanalytic theory.